Analysis of Students' Errors in Solving Mathematics Story Problems on the System of Linear Equations with Two Variables - Wibowo, Ari; SYAEKHU, Ahmad; AMIN, Rahmasinar (RADINKA JAYA UTAMA PUBLISHER, 2024)
This research aims to describe the types of errors and the causes of students making mistakes in solving mathematics story problems. The research method used is qualitative descriptive research. The population of this research was students in Makassar with a total of 23 students and 2 students were determined as the research sample. The results of the research found that most students experienced errors due to a lack of understanding of the existing material and behavior that tended to be careless and hasty so they made mistakes in solving math story problems. There were 4 types of student errors, namely (1) errors in reading the questions occurred because the participant's students failed to understand the content or meaning of story problems and were not able to identify relevant information in mathematics story problems (2) Conceptual errors occur because students do not understand and master the concepts of the material being taught so they are confused when determining what method is appropriate for solving story problems mathematics, (3) errors in procedures/steps occur. After all, students are not careful in carrying out calculation operations. This can be seen in the ability test of students who make calculation errors in the stages of solving story problems. (4) Errors in concluding occur because students think that concluding is not important, they assume that if they have got the final score from the calculation then the solution to the story problem has been completed.